A novel bioreactor and culture method drives high yields of platelets from stem cells - Avanzi, Mauro P.; Oluwadara, Oluwasijibomi E.; Cushing, Melissa M.; Mitchell, Maxwell L.; Fischer, Stephen; Mitchell, W. Beau (Transfusion (Philadelphia, Pa.), 2016)
BACKGROUND Platelet (PLT) transfusion is the primary treatment for thrombocytopenia. PLTs are obtained exclusively from volunteer donors, and the PLT product has only a 5‐day shelf life, which can limit supply and result in PLT shortages. PLTs derived from stem cells could help to fill this clinical need. However, current culture methods yield far too few PLTs for clinical application. To address this need, a defined, serum‐free culture method was designed using a novel bioreactor to increase the yield of PLTs from stem cell‐derived megakaryocytes. STUDY DESIGN AND METHODS CD34 cells isolated from umbilical cord blood were expanded with a variety of reagents and on a nanofiber membrane using serum‐free medium. These cells were then differentiated into megakaryocytic lineage by culturing with thrombopoietin and stem cell factor in serum‐free conditions. Polyploidy was induced by addition of Rho kinase inhibitor or actin polymerization inhibitor to the CD41 cells. A novel bioreactor was developed that recapitulated aspects of the marrow vascular niche. Polyploid megakaryocytes that were subjected to flow in the bioreactor extended proPLTs and shed PLTs, as confirmed by light microscopy, fluorescence imaging, and flow cytometry. RESULTS CD34 cells were expanded 100‐fold. CD41 cells were expanded 100‐fold. Up to 100 PLTs per input megakaryocyte were produced from the bioreactor, for an overall yield of 106 PLTs per input CD34 cell. The PLTs externalized P‐selectin after activation. DISCUSSION Functional PLTs can be produced ex vivo on a clinically relevant scale using serum‐free culture conditions with a novel stepwise approach and an innovative bioreactor.